Body mass index and peer victimization: A transactional model. Issue 2 (17th December 2020) - Thakkar, Niharika; van Geel, Mitch; Malda, Maike; Rippe, Ralph C. A.; Vedder, Paul
Abstract: Past research has shown concurrent associations between adolescent's body mass index (BMI) and classroom bullying victimization experiences. The goal of this three‐wave longitudinal study is to examine a transactional model of associations between BMI and bullying victimization among adolescents in India. We investigate concurrent unidirectional and bidirectional relations between BMI and victimization. In a sample of 1238 students from nine schools (Grades 7–9; M ‐ageT1  = 13.15, SD  = 1.16) in Indore, India, we used self‐ and peer‐reports to measure bullying victimization in the classroom, and objective measurement of students' height and weight to collect data on adolescents' BMI, across three waves in one school year. Structural equational modeling was used to test transactional relations between BMI and bullying victimization. For self‐reported victimization, there was no concurrent or over time association between BMI and victimization for boys or girls in the present study. For peer‐reported victimization, we observed concurrent associations between BMI and victimization for boys and girls and a prospective relation where higher BMI corresponded to less victimization over time for boys. The study yielded mainly concurrent relations between BMI and victimization among adolescents in India. Results from western countries may not generalize to India.